(untitled) (Faridpur Medical College Journal, 2021)
Chronic low back pain (CLBP) is an important health problem in Bangladeshi adult males. This case control study was carried out in the department of Physical Medicine and Rehabilitation, BSMMU, Dhaka from January 2015 to December 2015 to determine the association between CLBP and family history, smoking, level of education, level of income, level of exercise, bad posture and BMI in adult male. Total 171 patients with CLBP were taken as cases, and 171 male without CLBP were taken as controls. Data were collected using a structured interviewer-administered questionnaire, enquiring about demographic data and details of risk factors. Heights and weights were measured to calculate body mass index (BMI). Age range was 18 to 60 years. Mean age (± SD) for cases was 35.8±11 years and that of controls was 37.2±13 years. It was found that Bad posture (p value <.001), lack of exercise (p value<.001) and moderate level of education (p value .044) were significant risk factors for CLBP. Family history, smoking, level of income and BMI did not have a significant association with CLBP. Faridpur Med. Coll. J. 2020;15(2): 74-78